Assessment of Multi-trace Elements Level in Drinking Water Based on Ground Water Sources - Farahmand, Farhang; Pirumyan, Gevorg; Farahmand Ghavi, Farhid (Asian Journal of Chemistry, 2011)
The heavy metal trace elements and their concentrations in drinking water were determined at 7 sampling stations in north Tehran suburbs during fall and winter of year 2008-2009. The level of elemental concentration of each metal was determined by an inductively coupled plasma atomic emission spectrometry instrument (ICP-AES) according to standard sampling and measurement methods. The results showed that the concentration range of Al, Ni and B in drinking water was in the given order of 119-210, 2.8-20.40 and 123-1000 μg/L, which are above WHO standards guideline. The concentrations of other metals such as zinc, copper, vanadium and manganese were below the critical values. The phosphate and nitrogen fertilizers could be the major sources of heavy metals' presence in drinking water of the areas under water pollution assessment.